2019
DOI: 10.1159/000501119
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Cervical Lymph Node Sampling Performed by Respiratory Physicians

Abstract: Background: A variety of disease processes investigated by respiratory physicians can lead to cervical lymphadenopathy. Ultrasound (US) has revolutionised respiratory investigations, and neck ultrasound (NUS) is increasingly recognised as an additional important skill for respiratory physicians. Objectives: We aimed to assess the feasibility of NUS performed by respiratory physicians in the workup of patients with mediastinal lymphadenopathy. Methods: This is a single-centre retrospective cohort study. All pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Focused ultrasound performed by pulmonologists of structures related to the chest (e.g. neck) and subsequent ultrasound-guided biopsy has been described and potentially provides a rapid, less invasive method for obtaining a diagnosis and staging patients with suspected thoracic malignancy [250][251][252][253]. In addition, a potential role has been described in other diseases with extrapulmonary involvement (e.g.…”
Section: Overview Of the Evidence And Current Practicementioning
confidence: 99%
“…Focused ultrasound performed by pulmonologists of structures related to the chest (e.g. neck) and subsequent ultrasound-guided biopsy has been described and potentially provides a rapid, less invasive method for obtaining a diagnosis and staging patients with suspected thoracic malignancy [250][251][252][253]. In addition, a potential role has been described in other diseases with extrapulmonary involvement (e.g.…”
Section: Overview Of the Evidence And Current Practicementioning
confidence: 99%
“…Furthermore, carrying out an US-guided biopsy before giving systemic treatments can improve the quality of the biopsy specimen as high-dose steroids and radiotherapy can degrade the specimen [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neck LN sampling by respiratory physicians attending lung cancer fast-track clinic is feasible and safe – adding to an increasing body of evidence [10, 12]. Rapid diagnosis with a median time from referral to pathological confirmation of malignancy of 7 days means treatment decisions can be made with the current aspirational national targets (ref rapid pathway – 9 days) [3].…”
Section: Discussionmentioning
confidence: 99%
“…The Royal College of Radiology (RCR) guidelines for thoracic ultrasound performed by physicians lists NUS and biopsy as part of the competencies required to attain level 2 proficiency [11]. It has been shown that respiratory physicians are able to perform neck nodal sampling efficiently and safely after appropriate training [12]. In the setting of fast-track clinics, the availability of appropriately trained respiratory physicians, who typically see patients upon referral to the cancer pathway, allows examinations and sampling to be performed immediately, streamlining the diagnostic pathway and reducing waiting times for diagnosis.…”
Section: Introductionmentioning
confidence: 99%